A Welfare Based Approach for choosing the Inflation Targeting and the Exchange Regime in Tunisia - Soulaima, Abdelli (Journal of Economics and Behavioral Studies, 2014)
The inflation targeting is considered as an attractive monetary policy strategy in order to handle the inflation rate and improves the credibility of the central bank. The paper provides a stochastic dynamic general equilibrium model with the specificity of employing a small open economy. This model analyzes the impact of different regimes of inflation targeting and exchange rate in Tunisia in terms of the welfare loss and describes some aspects of the Tunisian’s economy. The results displays that the social loss is higher under the managed exchange rate than the flexible exchange rate regime for all the shocks. Then in terms of the inflation targeting index, it demonstrates that the consumer prices index outperforms the domestic inflation except for the productivity shock, in contrast to the result of (Parrado, 2004). Finally the strict is superior to the flexible inflation targeting except with the foreign inflation and the domestic interest rate shock.